The Role of Nitric Oxide in Nitrogen Fixation by Legumes - Signorelli, Santiago; Sainz, Martha; Tabares-da Rosa, Sofía; Monza, Jorge (Frontiers in Plant Science, 2020)
The legume-rhizobia symbiosis is an important process in agriculture because it allows the biological nitrogen fixation (BNF) which contributes to increasing the levels of nitrogen in the soil. Nitric oxide (·NO) is a small free radical molecule having diverse signalling roles in plants. Here we present and discuss evidence showing the role of ·NO during different stages of the legume-rhizobia interaction such as recognition, infection, nodule development, and nodule senescence. Although the mechanisms by which ·NO modulates this interaction are not fully understood, we discuss potential mechanisms including its interaction with cytokinin, auxin and abscisic acid signalling pathways. In matures nodules, a more active metabolism of ·NO has been reported and both the plant and rhizobia participate in ·NO production and scavenging. Although ·NO has been shown to induce the expression of genes coding for NITROGENASE, controlling the levels of ·NO in mature nodules seems to be crucial as ·NO was shown to be a potent inhibitor of NITROGENASE activity, to induce nodule senescence, and reduce nitrogen assimilation. In this sense, LEGHEMOGLOBINS (Lbs) were shown to play an important role in the scavenging of ·NO and RNS, potentially more relevant in senescent nodules. Even though ·NO can reduce NITROGENASE activity, most reports have linked ·NO to positive effects on BNF. This can relate mainly to the regulation of the spatiotemporal distribution of ·NO which favours some effects over others. Another plausible explanation for this observation is that the negative effect of ·NO requires its direct interaction with nitrogenase, whereas the positive effect of ·NO is related to its signalling function, which results in an amplifier effect. In the near future, it would be interesting to explore the role of environmental stress-induced ·NO in BNF.